Advances in Hydrogel Bioprinting for Bone Tissue Engineering - Bastami, Farshid (Journal of Dental School, 2024)
Bone regeneration is a complex process involving the orchestration of multiple cellular and molecular events. In recent years, significant interest has emerged in utilizing three-dimensional (3D) printed hydrogels for bone tissue engineering, owing to their potential in mimicking the natural extracellular matrix and providing a platform for cell growth and differentiation. The use of bioprinted hydrogels for bone regeneration has garnered attention due to its potential in addressing critical-sized bone defects.